Pela Gandong: Sebuah Upaya Mengkomunikasikan Kristus Ke Dalam Budaya Di Maluku - Camerling, Yosua Feliciano (STFT Jakarta, Indonesia, 2025)
Pela Gandong is a traditional kinship system indigenous to Maluku that has demonstrated a sustained capacity for maintaining social harmony and mediating conflict across communities, including between Muslim and Christian communities. Despite this significance, its potential as a bridge for Gospel communication within the framework of Indonesian contextual theology has not been systematically examined through an adequate cross-cultural communication framework. This study aims to analyze the values embedded in Pela Gandong and to assess their relevance as a medium for communicating Christ to the Malukan community. Drawing on a descriptive-qualitative approach and library research method, the study interprets Pela Gandong through the cross-cultural communication framework of David J. Hesselgrave. The study finds that Pela Gandong embodies three core values — social harmony, conflict mediation, and the instrumentalization of peace — that correspond substantively to Christian teachings on love, reconciliation, and shalom. This correspondence constitutes a theological point of contact through which the Gospel can be communicated contextually and organically, without compromising the integrity of local culture. These findings suggest that Pela Gandong can function as a legitimate cultural bridge in contextual missiological practice in Maluku, while also offering a replicable model for analogous approaches in other pluralistic cultural contexts across Indonesia.